Increased proportion of the CD56bright NK cell subset in patients chronically infected with Hepatitis C Virus (HCV) receiving interferon-a and ribavirin therapy - Lee, S.; Watson, M.; Flexman, J.; Cheng, W.; Hammond, T.; Price, Patricia (WILEY-LISS, 2010)
Natural killer (NK) cells are implicated in the regulation of a protective immune response in patients chronically infected with hepatitis C virus (HCV), but effects of interferon-a/ribavirin therapy on NK cell subsets and the consequences of viral clearance during therapy remain unclear. Samples were collected from chronically infected patients (n = 34) at baseline and from a subset after 3-10 months on pegylated interferon-a and ribavirin therapy (n = 19). NK cells present in cryopreserved PBMC were characterized by flow cytometry. Before therapy, the frequency of CD3-CD56+ NK cells was lower in patients than uninfected controls. Therapy increased proportions of CD56 bright NK cells. Frequencies of CD56dim NK cells declined slightly while perforin and CD16 expression on CD56dim NK cells decreased compared to baseline samples. Evaluation of NK cell subsets at baseline did not identify patients able to achieve sustained virological response following therapy. However, therapy may promote the expansion of NK cells able to produce interferon-?, while minimizing cytotoxicity to limit liver damage. © 2010 Wiley-Liss, Inc.